Lack of access to an open water source for bathing inhibited the development of the preen gland and preening behavior in Sanshui White ducks - Jiandui Mi; Hongling Wang; Xiaohui Chen; Kate Hartcher; Yan Wang; Yinbao Wu; Xindi Liao (Poultry Science, 2020)
As a species of waterfowl, ducks rely on access to water to facilitate feeding behaviors. Further, wet preening behavior in ducks relies on access to water and is a key behavior for duck welfare. Traditionally, Chinese duck farms provide not only free access to drinking water in the duck house but also an open water pool outside of the house. However, recent restrictions prohibit the use of an open water pool for raising ducks in some areas of China. Little is known about the effects of not providing an open water pool on duck welfare, in particular, the development of the preen gland and wet preening behaviors. The preen gland secretes oil which is crucial for maintaining plumage conditions. A total of one hundred twenty 1-day-old Sanshui White ducks (SSWD) were randomly divided into 2 groups and fed for 6 wk with access to a water pool (WP) or without access to a water pool and provided drinking water only (LWP). The live body weights of ducks from the WP group were significantly increased compared with those of ducks in the LWP group starting from 3 wks of age (P < 0.05). Feed intake was increased in the WP group at 2 wk of age and from 4 to 6 wk of age (P < 0.05). The feed conversion ratio (FCR) was significantly different only at 4 and 5 wks of age, when the FCR was increased by 5.7% and 9.5%, respectively, in the LWP group compared with the WP group (P < 0.05). Lack of access to an open water pool significantly inhibited the growth of the preen gland based on its weight, size, and quantity of oil secretions (P < 0.05). In addition, the proportion of ducks exhibiting wet preening behavior was significantly reduced in the LWP group compared with the WP group (5.5 ± 0.2% vs. 24.8 ± 2.1%, P < 0.05). This study indicated that a lack of access to an open water source had negative impacts on the development of the preen gland and on the preening behavior of SSWD.